RODERICK’S PERSONA AND SHADOW REPRESENTED IN EDGAR ““THE FALL OF THE HOUSE OF USHER” BASED ON CARL JUNG’S ARCHETYPES CHARACTERS - SUKSMANA, ROFIQ INDRA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Gothic is one of the most famous genres in literary work to describe romantic tragedy. Gothic contains elements are related to mysterious atmosphere, unreal situation, or distorted character. The Fall of the House of Usher is one example of Gothic stories which was firstly published in 1839. It tells about the story of twins who suffer mental illness. Roderick, as the main character, has two different sides of characteristic which makes him imbalanced. He does not recognize his own personality.This study uses archetypes characters theory to describe the characteristics of a person based on the ancient picture of the character that is used for theatrical performances in the past. The archetype of persona and shadow are selected in this study and subsequently used to identify two elements of the self-realization of the character.Archetype of persona is explained through the combination of Roderick’s face that resembles the image of an angel, but also, looks strange. Archetype of shadow is described through the creepy expressions of the voice, the bad attitude when he buries her sister alive, the wrong mindset about the existence of other God, as well as the wrong perception about things that unreal. The result of the study shows that shadow is a dominant than persona. Roderick was unable to identify the shadow, so that self-realization cannot be achieved. Archetypes anima/animus was needed to achieve self-realization in balance composition together with persona and shadow.Key Words : Archetypes Character, Persona, Shadow, Self-Realization